Lobbying for Subsidies with Heterogeneous Firms - Hannes Kammerer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Recent empirical evidence shows that the few firms that receive subsidies are large, and that large firms take a prominent role in shaping public policy by lobbying. In this paper, I present a theoretical framework that accounts for these empirical facts in a unified way. I study the role of firm heterogeneity in productivity for within-industry lobby formation when receiving subsidies and lobbying is costly. Due to firm heterogeneity, a within-industry conflict between receiving and non-receiving firms arises. This conflict creates lobbying incentives for large firms and delivers novel results. Surprisingly, increasing the barriers to lobby or lower firm heterogeneity amplifies this within-industry conflict such that a smaller lobby can attain a higher subsidy rate. Even if barriers to participate are modest, introducing a subsidy program harms particularly the smallest firms in a market.
Keywords: D72; H25; L11; 330